OPTIMIZING THE IMPLEMENTATION OF QUANTUM LEAP PROGRAM TO FACE THE CHALLENGES OF ASEAN OPEN SKY POLICY: LESSONS FROM GARUDA INDONESIA - Andhita Zerlina; Endi Haryono; Witri Elvianti (AEGIS : Journal of International Relations, 2016)
By the implementation of ASEAN Economic Community in 2015, all ASEAN member countriesare preparing themselves to survive in the economic competition including the aviation sector through ASEAN Open Skies Policy 2015. As the Indonesian national carrier, Garuda Indonesia has significant efforts in various sectors to support Indonesia in ASEAN Open Skies Policy 2015. The focus of this research is to critically examine the implementation of Garuda Indonesia’s Quantum Leap Program in supporting Indonesia in the implementation of ASEAN Open Sky Policy in 2015. This research also refers to several concepts such as regionalism and cultural diplomacy to explain the phenomenon of ASEAN Economic Community in which Garuda Indonesia displays its roles to promote Indonesia to foreign public.